2014
DOI: 10.11646/zootaxa.3785.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in Tripedaliidae (Conant 1897) (Cnidaria, Cubozoa, Carybdeida)

Abstract: The family Tripedaliidae was re-defined and expanded based on a molecular phylogenetic hypothesis by Bentlage et al. (2010, Proceedings of the Royal Society Biological Science, 277: 497). Additionally, Bentlage et al. (2010) proposed that all members of the family Tripedaliidae present dimorphism in gonads and have structures that function as seminal vesicles (at least in males). Until now, no information on Tripedalia binata concerning gonad morphology, sexual dimorphism, spermatophore formation or structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…Our results show that the male gonads of T. cystophora and C. sivickisi are similar corroborating previous results (Straehler‐Pohl, Garm, & Morandini, ). In both cases, the sperm matures in chamber‐like structures of the gonads and at any given time less than half the sperm cells are mature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that the male gonads of T. cystophora and C. sivickisi are similar corroborating previous results (Straehler‐Pohl, Garm, & Morandini, ). In both cases, the sperm matures in chamber‐like structures of the gonads and at any given time less than half the sperm cells are mature.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been suggested that the isorhizas are used to anchor the spermatozeugmata to the female tentacles during mating (Garcia‐Rodriguez et al, ), but these hypotheses are not mutually exclusive. Only ripe sperm cells are included in the spermatozeugmata leaving the immature sperm behind in the hemi‐gonad and each hemi‐gonads can thus form several spermatozeugmata over time (present work, Straehler‐Pohl et al, ; Garcia‐Rodriguez et al, ). This strongly suggests that even though the female of T. cystophora only mates once (Werner, ), the male can have multiple matings like seen for C. sivickisi (Lewis & Long, ).…”
Section: Discussionmentioning
confidence: 82%
“…Findings thus far suggest that the vast majority of staurozoans, cubozoans, and scyphozoans are gonochoristic (i.e., polyps give rise to medusae of a single sex) (Fig. B) (Berrill, ; Arai, ; Morandini and Da Silveira, ; Straehler‐Pohl et al, ), although sequential hermaphroditism has been reported in the scyphozoan Chrysaora hyoscella (Berrill, ).…”
Section: Cnidarian Sexual Systems: Multiple Transitions Between Gonocmentioning
confidence: 99%
“…Campbell (1974: 142) stated that gonads in most cnidarians are not separate organs, as found in higher animals, because germ cells are generally found in the interstitial portions of the body tissue which, prior to the formation of germ cells, exhibit no reproductive specialization. However, we follow Campbell (1974), Marques & Collins (2004), Bentlage et al (2010), Morandini & Marques (2010) and Straehler-Pohl et al (2014) in using the term gonad to refer to areas where gametes are formed.…”
Section: Identification Of Characteristicsmentioning
confidence: 99%